Manipulação e visualização de dados geográficos baseado em uma arquitetura serverless - Gasparin, Eduardo (2023)
The interpretation of geographical data faces significant challenges due to the heterogeneity of sources and formats. Disparity in the structures and origins of this data can complicate the analysis and understanding of the information contained in these databases, hampering the assessment of scenarios and decision-making processes. An effective approach to mitigate these challenges involves the adoption of visual representations, with an emphasis on the use of interactive maps. By being grounded in intuitive visual elements, this approach makes information accessible and facilitates the identification of spatial patterns and relationships between different variables, con- tributing to a more intuitive and effective interpretation. The present work outlines the specifications and implementation steps of a geographical data portal in the Amazon Web Services (AWS) environment, utilizing serverless architecture for the construction of an API dedicated to processing geographical information, and exposing it through a layer of visualization and interaction with the user. Additionally, this work elucidatesthe advantages related to serverless computing in processing data requests on a web platform, with experimental results demonstrating the efficiency of the implementation proposed in this work, solidifying it as a suitable and advantageous strategy in constructing this application model in a web environment.